Cardiovascular Reactivity and its Association with the Risk of Cardiovascular Morbidity - Milagros Lisset León Regal; Mikhail Benet Rodríguez; Cynthia Olivia Morales Pérez; Rosmari Álvarez Hernández; Yudith Brito Pérez de Corcho; José Omar de Armas García (Revista Finlay)
Background: there are no studies that confirm the association between cardiovascular hyperreactivity and the risk of cardiovascular morbidity. Objective: to determine the association between cardiovascular hyperreactivity and the risk of cardiovascular morbidity in normotensive individuals. Methods: a cross-sectional, correlational study was conducted. The universe consisted of the population aged 15 to 74 years in Cienfuegos municipality; the sample included 644 people. The variables were: sex, skin color, age, total cholesterol, HDL cholesterol, fasting blood glucose, smoking, baseline systolic blood pressure, cardiovascular reactivity, and risk of cardiovascular morbidity. The risk of cardiovascular morbidity was calculated by applying the Framingham Risk Functions. The Pearson’s Chi-square test and the prevalence ratio were used with a 95 % confidence interval. The direction of the relationship between cardiovascular reactivity, age, and systolic blood pressure was analyzed considering the Eta value. Results: the prevalence of cardiovascular hyperreactivity was higher among people aged 65 to 74 years and males. A higher risk of cardiovascular morbidity was observed in cardiovascular hyperreactive individuals. There is an association between non-optimal systolic blood pressure, increasing age, and high risk of cardiovascular morbidity in cardiovascular hyperreactive people. Conclusions: the risk of cardiovascular morbidity is higher in cardiovascular hyperreactive individuals than in normoreactive people. Age and systolic blood pressure showed greater association with high risk of cardiovascular morbidity.